PENGARUH KOMPRES KAYU MANIS (Cinnamomum burmannii) TERHADAP NYERI GOUT ARTHRITIS PADA LANSIA - Fera Siska; Evi Royani; Italia (Jurnal Kesehatan dan Pembangunan, 2026)
Gout arthritis is a metabolic disease often experienced by the elderly due to the accumulation of uric acid crystals in the joints, causing pain, swelling, and limited activity. Untreated pain can reduce the quality of life of the elderly. One non-pharmacological approach to reducing gout arthritis pain is applying a cinnamon (Cinnamomum burmannii) compress, which has anti-inflammatory and analgesic effects. Objective This study aims to determine the effect of cinnamon compresses on gout arthritis pain in the elderly at the Harapan Kita Social Home for the Elderly in Palembang. Method the research method used is quantitative research with a quasi-experimental design usingone group pretest-posttest approachThe study was conducted on November 20–25, 2025. The population in this study were all elderly people with gout arthritis, with a sample of 20 respondents selected using a purposive sampling technique. Pain levels were measured before and after the cinnamon compress application using a numeric pain scale. The results study results showed a decrease in gout arthritis pain levels in the elderly after cinnamon compresses were administered. Statistical tests showed a p-value <0.05, indicating that cinnamon compresses had an effect on reducing gout arthritis pain in the elderly. The conclusion of this study is that cinnamon (Cinnamomum burmannii) compresses are effective in reducing gout arthritis pain in the elderly. Cinnamon compresses can be used as a non-pharmacological intervention in nursing practice to help reduce pain and improve comfort in elderly people with gout arthritis